Gambaran Penggunaan Rapid Diagnostic Test Parasit Malaria Di Desa Pasirmukti Kecamatan Cineam Kabupaten Tasikmalaya - Hubullah Fuadzy; Marliah Santi (ASPIRATOR - Journal of Vector-borne Disease Studies, 2013)
High mobility amongst mining workers, demanding officer of Cineam Public Health Center can perform rapid diagnosis to the workers. Nowadays, many techniques are developed to detect the early transmission of malaria, begins from the clinical to the molecular, one of that techniques are Rapid Diagnostic Tests (RDTs). This research has been conducted in the village of Pasirmukti district Cineam, Tasikmalaya in 2012. Objective of this paper is description RDT utilities as rapid diagnosing efforts on families who have family members as mine worker malaria endemic areas. Inclusion criteria for this study were family who have and do not have family members were working as workers in malaria-endemic areas at 2011 or 2012. Respondents were willing to participate in this study would be taken for examination RDT. Respondents were willing to participate in this study amounted to 256 people, and 5 of them positive Plasmodium malaria based on RDTs screening. Respondents who positive for malaria on RDTs test were 4 women with lower education background and work as a housewife, then a men with a background of secondary school education and are currently still as student. RDT is one of the malaria parasite tools which suitable for use in the Pasirmukti Village district Cineam - Tasikmalaya. However, keep in mind on how to storage and use in order to avoid errors both false-positive and false negatives test results.